2016
DOI: 10.3892/or.2016.5262
|View full text |Cite
|
Sign up to set email alerts
|

BMI-1 interacts with sMEK1 and inactivates sMEK1-induced apoptotic cell death

Abstract: The B lymphoma Mo-MLV insertion region 1 homolog (BMI-1) protein is activated in various types of tumors and associated with cancer development and tumor progression. However, the working role of BMI-1 in cellular signaling is not understood completely. In this study, we revealed one possible biologic mechanism of BMI-1 in cancer progression in vitro using a human ovarian tumor cell system. Suppressor of MEK1 (sMEK1), a pivotal regulator involved in the cellular biological response mechanism, was identified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…In accordance, other studies found that BMI1 was involved in inducing epithelial mesenchymal transition, leading to tumor invasion and metastasis [ 26 ]. Moreover, over-expression of BMI1 in EOC cells was found to up-regulate the expression of cyclin D1, CDK4 and Bcl-2, promoting cell growth and inhibiting cell apoptosis [ 27 ]. In contrast, silencing BMI1 in our study manifested a reverse impact on regulation of the cell cycle and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, other studies found that BMI1 was involved in inducing epithelial mesenchymal transition, leading to tumor invasion and metastasis [ 26 ]. Moreover, over-expression of BMI1 in EOC cells was found to up-regulate the expression of cyclin D1, CDK4 and Bcl-2, promoting cell growth and inhibiting cell apoptosis [ 27 ]. In contrast, silencing BMI1 in our study manifested a reverse impact on regulation of the cell cycle and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 90 , 91 , 92 , 93 ]. Bmi-1 can also activate the PI3K/mTOR/4EBP1 signaling pathway in ovarian cancer cells to regulate cell proliferation [ 94 ]. N-acetylglucosamine transferase (OGT) is the only known enzyme to catalyze the O-GlcNAcylation in humans.…”
Section: Bmi-1-targeted Processes In Cancermentioning
confidence: 99%
“…Previous studies have found the overexpression of BMI‐1 in many cancers and tumor cells and have suggested that BMI‐1 may be a new target for the treatment of many types of cancers and tumors [13–15]. Recently, the effects of BMI‐1 gene silencing on cell cycle and apoptosis rate were confirmed in cancer cells [16]. A high BMI‐1 protein expression was detected in many hematopoietic and malignant solid tumors; thus, the crucial role of BMI‐1 in the treatment of many tumors has been suggested [17].…”
Section: Introductionmentioning
confidence: 98%